2001
DOI: 10.1074/jbc.m008564200
|View full text |Cite
|
Sign up to set email alerts
|

Transendothelial Migration of Colon Carcinoma Cells Requires Expression of E-selectin by Endothelial Cells and Activation of Stress-activated Protein Kinase-2 (SAPK2/p38) in the Tumor Cells

Abstract: Adhesion and migration of tumor cells on and through the vascular endothelium are critical steps of the metastatic invasion. We investigated the roles of E-selectin and of stress-activated protein kinase-2 (SAPK2/p38) in modulating endothelial adhesion and transendothelial migration of HT-29 colon carcinoma cells. Tumor necrosis factor ␣ (TNF␣) strongly increased the expression of E-selectin in human umbilical vein endothelial cells (HUVEC). This effect was independent of the activation of SAPK2/p38 induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 52 publications
3
107
0
3
Order By: Relevance
“…Activation of E-selectin by crosslinking antibodies or adhesion of colon cancer cells triggers the activation of ERK and p38 MAP kinases in endothelial cells Transendothelial migration of colon cancer cells depends on motogenic signals that result from their adhesion to E-selectin expressed by endothelial cells (Laferrie`re et al, 2001). In the present work, we investigated whether the adhesion of colon cancer cells to E-selectin also induced in endothelial cells a forward signalling that leads to the formation of breaches in the endothelial layer, thereby facilitating invasiveness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of E-selectin by crosslinking antibodies or adhesion of colon cancer cells triggers the activation of ERK and p38 MAP kinases in endothelial cells Transendothelial migration of colon cancer cells depends on motogenic signals that result from their adhesion to E-selectin expressed by endothelial cells (Laferrie`re et al, 2001). In the present work, we investigated whether the adhesion of colon cancer cells to E-selectin also induced in endothelial cells a forward signalling that leads to the formation of breaches in the endothelial layer, thereby facilitating invasiveness.…”
Section: Resultsmentioning
confidence: 99%
“…It requires specific interactions between adhesion receptors present on vascular endothelial cells and their counter-receptors on cancer cells (Haier and Nicolson, 2001). These adhesive interactions induce a reverse signalling in the cancer cells that increases their motile potential and a forward signalling in endothelial cells that elicits breaches in the endothelium layer (Hu et al, 2000;Laferrie`re et al, 2001;Weis et al, 2004). However, in both cases the signalling mechanisms involved are still ill defined.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify details with reference to signal transduction, we focused attention on the p38/Hsp27 pathway. It is known that binding of sialyl-Le a and sialyl-Le x to E-selectin activates p38 signaling in cancer cells (12,39), resulting in stimulation of phosphorylation of various transcription factors and MAPKAP kinase 2, with subsequent activation of MAPKAP kinase 2 and Hsp27, the actin polymerizing factor (40). To investigate the influence of NEU4S on cell motility, HT29 cells were stimulated with E-selectin and the phosphorylation levels were assessed.…”
Section: Neu4s Suppresses E-selectin-induced Cell Motility Through Acmentioning
confidence: 99%
“…In normal colon mucosa, the expression of sialyl-Le a and sialyl-Le x is quite low, whereas more complicated carbohydrates, such as disialyl-Le a and sialyl-6-sulfo-Le x , are major components (9,10). Sialyl-Le a and sialyl-Le x play an important role, as carbohydrate ligands for E-selectin, in E-selectin-mediated cancer cell adhesion to vascular endothelial cells during the course of hematogenous metastasis (11), through activation of the SAPK/p38 signaling pathway (12,13). On the other hand, disialyl-Le a , sialyl-6-sulfoLe x , Le a , and Le x do not bind to E-selectin.…”
mentioning
confidence: 99%
“…SL X expression is increased in human hepatic colorectal metastases compared to the primary tumour (Hoff et al, 1989) and expression has been shown to correlate with poor survival of colorectal cancer patients (for example, in stage III patients 5 year survival was 42% in the sL X positive group vs 81% in patients with tumours negative for sL X in one study) (Nakamori et al, 1993). Expression of E-selectin on endothelial cells has also recently been shown to be essential in models of transendothelial migration of colon carcinoma cells (Laferriere et al, 2001). Matsumoto et al (2001) have also retrospectively analyzed the patients in their previous study of cimetidine in colorectal cancer according to sL A and sL X expression.…”
mentioning
confidence: 99%